Chemical composition database establishment and metabolite profiling analysis of Yangyin qingfei decoction. (10th June 2019) - Zhang, Zheng; Tang, Yuqing; Yu, Bocheng; Ying, Jiaming; Wu, Bingchu; Wu, Jinyi; Zhao, Jinshun; Chen, Zhenjun; Xu, Jinyan; Tang, Chunlan
Abstract: The chemical fingerprinting and metabolite profile in a rat plasma sample after intragastric administration of Yangyin qingfei decoction (YYQFD, 14 g/kg) were investigated. First, YYQFD was analyzed by UPLC/Q‐TOF MS to establish the chemical composition database by comparing their retention behavior, accurate molecular mass and MS 2 data with those of references or known compounds in the literature. In this database, 100 chemical constituents with information on retention time, molecular mass, molecular formula, MS 2 data and compound name were identified, which can provide compound information for further metabolite profiling studies. Furthermore, 64 compounds including 37 prototypes and 27 metabolites were detected in the dosed rat plasma sample, and the metabolic pathways of YYQFD were hydrolyzation, hydroxylation, dehydrogenation, glucuronidation, glucosylation, sulfation and mixed modes. Among the five component herbs in the YYQFD, Glycyrrhizae Radix et Rhizome and Fritillariae Thunbergii bulbs were actively metabolized, contributing 16 and 7 metabolites, respectively. It is suggested that chemical characterization and metabolite profiling studies are valuable to elucidate the material basis of herbal preparations.